Evaluation of indicator tests for identification of segregation in flexible pavements : a case study - Hainin, Mohd. Rosli (Faculty of Civil Engineering, UTM, 2000)
Segregation of hot mix asphalt (HMA) is a continuing problem in construction practice which has caused premature distress in many flexible pavements. A study, funded by the Kansas Department of Transportation, was conducted on a newly constructed pavement to evaluate the effectiveness of indicator tests in detection of segregation. Cores were obtained from segregated and non-segregated areas of the pavement and the unit weights of the pavement were determined using a thin-lift nuclear gauge. The change gradation on the 4.75 mm sieve was compared with the indicator tests of asphalt content, i.e., nuclear gauge unit weight, core unit weight and macrotexture. The results of this study indicate that asphalt content is the best indicator test of segregation whilst macrotexture is the best non-destructive indicator test of segregation.